2008
DOI: 10.1016/j.radi.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based radiography

Abstract: Evidence-based practice (EBP) offers the integration of the best research evidence with clinical knowledge and expertise and patient values. EBP is a well known term in health care. This paper discusses the implementation of EBP into radiography and introduces the term evidence-based radiography. Evidence-based radiography is radiography informed and based on the combination of clinical expertise and the best available research-based evidence, patient preferences and resources available. In Norway, EBP in radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 39 publications
0
48
0
1
Order By: Relevance
“…Other learning needs are created by organisational or professional issues such as the introduction of new technologies or applications of technologies, project or research work, protocol development as well as formal study and require practitioners to access and use professionally relevant information. Indeed, each of the current professional drives of recognising or mandating that practitioners continue to update their professional knowledge, 22,23 increasing practitioner involvement in research [24][25][26][27][28][29] and utilising evidence based practice 30,31 (EBP) necessitate the need for MRS practitioners to have access to and use information sources that contain the multidisciplinary knowledge base of the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Other learning needs are created by organisational or professional issues such as the introduction of new technologies or applications of technologies, project or research work, protocol development as well as formal study and require practitioners to access and use professionally relevant information. Indeed, each of the current professional drives of recognising or mandating that practitioners continue to update their professional knowledge, 22,23 increasing practitioner involvement in research [24][25][26][27][28][29] and utilising evidence based practice 30,31 (EBP) necessitate the need for MRS practitioners to have access to and use information sources that contain the multidisciplinary knowledge base of the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Research within evidence-based radiography shows that mammographers today work evidence-based in a general way. However, according to Hafslund et al (2008), it is still not routine within radiography to actively search for research. This may be due to prerequisites such as time, money and https://journals.hioa.no/index.php/radopen/index attitudes which affect mammographers' possibilities, but it may also be due to norms (Ahonen & Liikanen, 2010).…”
Section: Screening Of Women With Breast Implantsmentioning
confidence: 99%
“…Th e participants could relate strongly to the concept of experience based knowledge and made an association to evidence based practice. 24 Marshall, Punys and Sykes 25 reported that 95 % of radiographers sampled believed that CPD was important or very important in radiography and that the preferred CPD activity was a combination of printbased, e-learning and internet based material. Th is is not consistent with our study fi ndings.…”
Section: Core Category: Important Learning Arenasmentioning
confidence: 99%